PENGARUH MEDIA TANAH DAN AKUAPONIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa), CAISIM (Brassica juncea L.), DAN PAKCOY (Brassica rapa chinensis) - Krisma Abeltino; Sugiyanto Sugiyanto; Harlina Kusuma Tuti (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2021)
Research to determine the effect of soil media and aquaponics on thegrowth and production of lettuce, caisim, and pakcoy. The growth and productionof lettuce, caisim, and pakcoy are influenced by several factors, one of which isthe planting media. This research was conducted in the experimental garden ofthe Faculty of Agriculture, University of Borobudur. The study was conducted inNovember 2019 until January 2020. The experimental design carried out in thisstudy was a 2 x 3 factorial in the Randomized Block Design (RBD) design. Thefirst factor is the planting media (soil, and aquaponics) and the second factor isthe type of plant (Lettuce, Caisim, and Pakcoy). Based on these two factors, 10plants were assigned to each sample unit, so that 10 x 18 = 180 sample plantswere determined. The sample plants were randomly determined fromexperimental plants other than marginal plants.The results showed that the planting media and plant types significantlyaffected the parameters of the number of leaves (strands), plant height (cm), rootlength (cm), root wet weight (grams), consumption wet weight (grams), root dryweight (grams), and consumption dry weight (grams). Aquaponic media treatmentof lettuce plants provides the best effect of the treatment of soil media on lettuceplants. The treatment of soil media on caisim plants gives the best effect from thetreatment of aquaponic media on caisim plants. Soil and aquaponic mediatreatments on Pakcoy plants were not significantly different in the parameters ofthe number of leaves, plant height, root length, and root dry weight.Key words: Aquaponics, Catfish, Growing media, Narrow land, Organicvegetables